Hemoglobin subunit beta protein as a novel marker for time since deposition of bloodstains at crime scenes. (July 2022) - Heo, Tae moo; Gwon, Sun-Yeong; Yang, Jung-Hyeon; Hyun, Sung Hee; Kang, Hee-Gyoo; Sung, Ho Joong
Abstract: Dried bloodstains at crime scenes provide abundant information for analyzing criminal identity of victims or suspects, morphological characteristics, and biological and chemical compounds. Therefore, they are considered important evidence by investigators at crime scenes. Moreover, the age of bloodstains can be used to determine the timeline of incidents at crime scenes; Inappropriately handled bloodstains may cause degradation of blood components. In this study, we identified a novel marker, hemoglobin subunit beta protein, as an internal standard to determine the age of bloodstains at crime scenes. We found that the target spot between 20 and 30 kDa in two-dimensional electrophoresis gradually increased in size. The hemoglobin subunit beta protein was identified from this spot using liquid chromatography-tandem mass spectrometry and verified using western blotting. Sample bloodstains were exposed to various environmental conditions (humidity: 30%, 60%, 90% at room temperature [RT]). Furthermore, the hemoglobin subunit protein extracted from the sample bloodstains at various time points (0 h to 30 d) was dissolved in our newly developed buffer solution and in deionized or distilled water. We also analyzed the expression levels of the protein in the sample bloodstains, dried at RT and under various humidity over time, using western blotting. In addition, we evaluated the protein extraction capacity of deionized or distilled water and the newly developed buffer from the sample bloodstains over time. At RT and 60% humidity, using the newly developed buffer, the hemoglobin subunit beta protein levels showed a gradually increasing pattern. Finally, we quantitated human hemoglobin subunit beta protein using western blotting and enzyme-linked immunosorbent assay, which revealed significant differences among the samples. In particular, the time points from 36 h to 30 days were considered for analysis. Thus, the hemoglobin subunit beta protein dried at RT and 60% humidity and further dissolved in the newly developed buffer solution can be used to determine the age of bloodstains at crime scenes. Highlights: Hemoglobin subunit beta protein levels in bloodstains increase over time. Hemoglobin subunit beta protein might be useful to understand the crime scene. Our newly developed buffer solution preserves protein stability in bloodstains.